ANALYSIS OF DATA MANAGER FOR ENGINEERING COLLEGE AN ANDROID APPLICATION - Deshmukh, Mrunal Abhijeet; Wadhekar, Arti. R.; Tupe, Durgesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In any engineering college storing data is a huge and crucial task they need an application which is secure, contains large storage capacity and easy to handle. So this paper introduces an application named "The Data Manager for Engineering College" an Android application which is able to store a huge amount of data, secured and has a user friendly interface with good features. This application can perform multiple tasks such as, giving a platform to teachers to manage student marks for various assessments, to provide a module to take and store attendance of students. Additionally, teachers can post notices and provide syllabus copies for each subject directly in this applications students will get all the material provided by teacher right after they download this application. The app also allows instructors to share daily notes regarding the concepts to be taught in class and includes a module for maintaining student attendance records. This application contains several modules such as student achievement module, internships and training module, students fees record module, student’s projects module, etc. The aim of this project is to help teachers to maintain student data in a single app and to help students to get notes, check marks, attendance, notices from teachers in a single app.